The United States, Iran and transatlantic relations: Headed for crisis? - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2004)
In the United States, the debate about how to deal with Iran has recently intensified. Firstly, speculation about the relationship between Iran and al-Qaeda was prompted by the report of the 9/11 Commission. A number of those who participated in the attacks left Afghanistan via Iran, but they received no Iranian stamp in their passports. Although according to U.S. intelligence circles this does not constitute an indication of Iranian cooperation with the terrorist network, it does seem to have confirmed Iran's image as a "terrorist state." Secondly, in a report published in July 2004 that has received considerable attention, the Council on Foreign Relations called for moving towards a policy of "selective engagement" and away from the hard-line policy of isolating and containing Iran. Thirdly, it appears that the European-Iranian agreement of fall 2003, in which Iran pledged to suspend all uranium enrichment and processing activities, has failed. As a result, the United States is increasing pressure on its European allies to take the issue to the UN Security Council with the ultimate aim of pushing through sanctions for breaking the non-proliferation treaty. With talk already underway of a burgeoning new crisis in the transatlantic relationship, there is reasonenough to analyze the development of American policy towards Iran and the options being discussed in the US in terms of their consequences for German and European policy. (SWP-Comments / SWP)
Keywords: 320